A qualitative study of dropout from an internet-delivered CBT intervention for adults with depression and anxiety - LAWLER, KATE (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2020)
Despite the efficacy and widespread use of online-delivered psychological interventions, treatment dropout remains a problem that for the most part is poorly understood. This qualitative study investigated the subjective experience of dropout from a supported iCBT programme for adults with depression and anxiety. This was a nested study part of a larger RCT investigating the (cost)effectiveness of iCBT for depression and anxiety in the UK?s Improving Access to Psychological Therapies programme. Fifteen purposively sampled participants (8 female) were interviewed via telephone using a semi-structured interview schedule that was developed from the existing research in the field. Data was analysed using the descriptive-interpretive approach. The experience of treatment leading to dropout can be understood in terms of ten domains: Relationship to Technology, Motivation to Start, Background Knowledge and Attitudes towards iCBT, Change in Motivation, Usage of the Programme, Changes due to the Intervention, Engagement with Content, Experience Interacting with the Supporter, Experience of Online Communication and Termination of the Supported Period. Dropout participants have a wide variety of experiences that are both positive and negative. Reported changes in motivation categorise dropout participants into two groups: those who feel ready to leave treatment early and those who have negative reasons for dropping out. The diversity of experiences and evidence of the role played by patient discretion in the decision to drop out brings into question the current conceptualisation of the phenomenon as a homogenous, negative construct. Dropout is a nuanced phenomenon, requiring further exploration in terms of its parameters and patient typology. Keywords: depression; anxiety; iCBT; dropout; internet interventions
DROPOUT FROM AN INTERNET-DELIVERED CBT INTERVENTION
APPROVED
Keywords: anxiety; iCBT; dropout; internet interventions; depression